Development, characterisation and biocompatibility analysis of a collagen-gelatin-hydroxyapatite scaffold for guided bone regeneration = Desarrollo, caracterización y análisis de biocompatibilidad de un andamio de colágeno-hidroxiapatita para la regeneración ósea guiada - Shankar, Preethi; Arumugam, Parkavi; Kannan, Saranya (2024)
Guided Bone Regeneration (GBR) is the choice of treatment for improving the horizontal and vertical bone volume through bone grafting. GBR membranes work on the principle of preventing epithelial migration into the defect space while maintaining the space for cell migration and differentiation at the defect site. Hydroxyapatite has been commonly used as a bone graft for infrabony defects. The study was conducted at the Department of Biomaterials at Saveetha Dental College. GBR membrane was prepared and its material characterization was done using Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX) analysis, Fourier Transform Infrared Radiation (FTIR), and Confocal Analysis. The developed GBR membrane revealed SEM properties conducive to cell attachment. EDX and FTIR analysis showed the successful development of the collagen-gelatin-hydroxyapatite membrane. Cell culture and confocal analysis revealed excellent biocompatibility with a homogenous layer of viable cells. The developed composite GBR membrane is a biogenic membrane with relevant biomineralization potential that should be applied for GBR applications.
La regeneración ósea guiada (GBR) es el tratamiento de elección para mejorar el volumen óseo horizontal y vertical mediante injertos óseos. Las membranas GBR funcionan según el principio de prevenir la migración epitelial hacia el espacio del defecto. La hidroxiapatita se ha utilizado habitualmente como injerto óseo para defectos infraóseos. El estudio se realizó en el Departamento de Biomateriales del Saveetha Dental College. Se preparó un scaffold o andamio, el cual se caracterizó mediante microscopio electrónico de barrido (SEM), análisis de rayos X de dispersión de energía (EDAX), radiación infrarroja por transformada de Fourier (FTIR) y análisis confocal. El andamio desarrollado reveló propiedades propicias para la unión celular. Los análisis EDAX y FTIR mostraron el desarrollo exitoso de la membrana de colágeno-gelatina-hidroxiapatita. El cultivo celular y el análisis confocal revelaron una excelente biocompatibilidad con una capa homogénea de células viables. El andamio desarrollado es una membrana biogénica con un potencial de biomineralización relevante que puede utilizarse para aplicaciones GBR.
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 14 de febrero, 2025
También disponible en formato HTML y EPUB